Statistical optimization of hexavalent molybdenum reduction by Serratia sp. strain MIE2 using Central Composite Design (CCD) - Aziz, Nor Farahim; Halmi, Mohd Izuan Effendi; Wan Johari, Wan Lutfi (Hibiscus Publisher, 2017)
The conversion of hexavalent molybdenum (Mo (VI)) to Mo-blue is a bioremediation techniquewhich reduces the toxicity of molybdenum to a less toxic form by bacteria. The aim of this studyis to determine the optimum conditions of significant parameters or variables that affect thereduction of Mo (VI) to Mo-blue by the local isolate identified as Serratia sp. strain MIE2.Response Surface Methodology (RSM) was used in this study to optimize the reduction processusing Central Composite Design (CCD) as an optimization matrix. The optimum conditionspredicted by RSM using the desirability function for the reduction process were 20 mMmolybdate concentration, 3.95 mM phosphate, 6.25 pH and 25 g/L glucose and Mo-blueproduction occurred at the absorbance value of 20.5 at 865 nm. The validation of the predictedoptimum points showed the Mo-blue production occurred at the absorbance value of 21.85 witha deviation around 6.6 % from the RSM predicted value.